2019
DOI: 10.1038/s41598-019-52145-1
|View full text |Cite
|
Sign up to set email alerts
|

The influences of gender and aging on optic nerve head microcirculation in healthy adults

Abstract: Potential differences in the nature of the influences of aging and gender on the optic nerve head (ONH) microcirculation, using laser speckle flowgraphy (LSFG) were evaluated. We studied 908 healthy subjects (men = 701, age: 50.0 ± 9.1 yrs, women = 208, 49.8 ± 9.5 yrs, p = 0.76). The average, maximum (Max), and minimum (Min) mean blur rate (MBR) in a heartbeat were evaluated. The parameters were analyzed separately for the tissue, vessels, and throughout the ONH (All). We investigated which MBR sections are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
13
1
2
Order By: Relevance
“…This difference is most likely explained by the higher age of BRVO patients when compared to the other groups and the well-documented finding that MBR decreases with age. 13,40 Notably, there was no correlation between RBF and age in either group, indicating that the metric is associated with disease-related differences rather than demographic changes. Age-related changes to MBR also highlight why it is useful to use the intrapatient control of patient's fellow eye when making comparisons of blood flow.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This difference is most likely explained by the higher age of BRVO patients when compared to the other groups and the well-documented finding that MBR decreases with age. 13,40 Notably, there was no correlation between RBF and age in either group, indicating that the metric is associated with disease-related differences rather than demographic changes. Age-related changes to MBR also highlight why it is useful to use the intrapatient control of patient's fellow eye when making comparisons of blood flow.…”
Section: Discussionmentioning
confidence: 92%
“…Analyses are additionally complicated by significant intersubject heterogeneity that goes beyond simple demographic differences. 27,28 Therefore the first aim of this study is to define a novel metric-relative blood flow (RBF)-and demonstrate how it effectively describes the impediment of retinal blood flow in patients with unilateral RVO. The second aim of this study is to compare this metric to known characteristics of RVOs and use it to help predict future outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We theorized that the variables of MBR waveform provide an indication of the systemic fluctuation of blood flow. A study showed that, in tissue regions, MBR max -increases while MBR min decreases with aging 23 , however, AC was not mentioned. In this study, we observed that the MBR max and MBR min increased while AC decreased in all regions over time.…”
Section: Discussionmentioning
confidence: 98%
“…Ageing increases the stiffness of ocular vessels and decreases the MBR. (23,24) We anticipated that short-term periocular massage can improve OBF variables, but there is no evidence for the improvement of OBF by chronic periocular massage at present.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis method was similar to those reported previously. (23,24) The software program selected the optic nerve head using the automated definitive threshold (Figure 2). The following indices were calculated from the obtained data: MBR which reflects the velocity of the OBF, blow-out time (BOT), and blow-out score (BOS).…”
Section: Ocular Blood Flow Recordingmentioning
confidence: 99%